Implementation of RFID-Based Attendance Integrated with Management Systems and Notifications via WhatsApp - Salsabila, Salsabila; Anwar, Anwar; Syahputra, Guntur (Journal of Artificial Intelligence and Software Engineering, 2024)
Currently, attendance recording faces challenges, especially with validation using Mac Addresses which is suboptimal due to the dynamic nature of device IP Addresses. To address this issue, the researcher proposes integrating the existing management system with RFID-based attendance. RFID technology enables tracking and identification using radio waves without direct contact, ensuring efficient and accurate attendance recording. The system will send attendance notifications to teachers via WhatsApp and store data in a database, facilitating monthly summaries and ensuring data security and availability for future reference. This research utilizes blackbox testing to evaluate system accuracy, achieving a 95% accuracy rate in RFID tag readings and successful RFID tag scanning processes. Network speed measurement using QoS shows favorable results, with a throughput of 77.4 Kbps, zero packet loss, an average delay of 1.919 ms, and jitter of 1.92 ms in tests involving 15 RFID tags